Symptom Burden and Quality of Life by Lymphedema Stage After Breast Cancer - Çağrı Akalın (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Breast cancer-related lymphedema (BCRL) is a chronic condition that contributes to symptom burden and impairs quality of life. This single-center cross-sectional study evaluated the association between the clinical stage of lymphedema, patient-reported symptom burden, and quality of life in 63 patients with BCRL. Lymphedema stage was classified according to the International Society of Lymphology (ISL) criteria, with 11 patients (17.5%) in Stage I, 39 (61.9%) in Stage II, and 13 (20.6%) in Stage III. Symptom burden and functional impairment were assessed using the Lymph-ICF-UL, and quality of life using the FACT-B+4. Group comparisons were performed using non-parametric methods, and multivariable linear regression was used to evaluate the independent association of clinical stage after adjustment for age, body mass index, radiotherapy, chemotherapy, lymph node count, diabetes, and lymphedema duration. Symptom burden and functional impairment increased with advancing stage (p<0.001): median Lymph-ICF-UL total scores rose from 16.0 (interquartile range [IQR]: 14.8-16.6) in Stage I to 47.8 (IQR: 47.0-50.6) in Stage III. Quality of life declined in parallel (p<0.001), with median FACT-B+4 scores decreasing from 115.2 (IQR: 110.4-118.5) in Stage I to 75.4 (IQR: 73.9-77.1) in Stage III. After multivariable adjustment, Stage III remained associated with higher Lymph-ICF-UL scores (β=32.57; 95% confidence interval [CI]: 30.09 to 35.06) and lower FACT-B+4 scores (β=−40.75; 95% CI: −46.25 to −35.25) compared with Stage I. These findings suggest a role for patient-reported outcome measures in the clinical assessment of BCRL and provide observational evidence for stage-related differences in patient experience, requiring confirmation in larger longitudinal cohorts.